Optimizing mycobacteria molecular diagnostics: No decontamination! Human DNA depletion? Greener storage at 4 °C! - Prajwal, Prajwal; Neary, Turlough; Rohrbach, Katja; Bittel, Pascal; Göller, Pauline C.; Buch, Thorsten; Dümcke, Sebastian; Keller, Peter M. (Frontiers in Microbiology, 2023)
Tuberculosis (TB) is an infectious disease caused by the group of bacterial pathogens Mycobacterium tuberculosis complex (MTBC) and is one of the leading causes of death worldwide. Timely diagnosis and treatment of drug-resistant TB is a key pillar of WHO’s strategy to combat global TB. The time required to carry out drug susceptibility testing (DST) for MTBC via the classic culture method is in the range of weeks and such delays have a detrimental effect on treatment outcomes. Given that genotypic testing is in the range of hours to 1 or 2 days its value in treating drug resistant TB cannot be overstated. In developing such tests, one wants to optimize each step so that tests are successful even when confronted with samples that have a low MTBC load or contain large amounts of host DNA. In this work we endeavor to optimize pre-treatment and extraction steps for such genotypic tests. We begin by choosing the best DNA extraction device by comparing the Ct (cycle threshold) values following extraction with five commonly used devices. Following this, we explore the effect decontamination and human DNA depletion have on extraction efficiency. The best results were achieved (i.e., the lowest Ct values) when neither decontamination nor human DNA depletion were used. Surprisingly, in all tested scenarios the addition of decontamination to our workflow increased Ct values. This goes against the well-established orthodoxy that decontamination should be performed prior to amplification of targets in MTBC. As a complement to the above experiments, we also considered the best Mycobacterium tuberculosis DNA storage method to optimize molecular testing carried out in the near- to medium-term. We compared Ct values following three-month storage at 4 °C and at -20 °C and found little difference between the two. In summary, for molecular diagnostics aimed at mycobacteria this work identifies an efficient DNA extraction device, indicates that decontamination causes significant loss of mycobacterial DNA, and shows that samples preserved for further molecular testing can be stored at 4 °C. Under our experimental settings, human DNA depletion gave no significant improvement in Ct values for the detection of MTBC.